Microbiological Air Quality in a Highschool Gym Located in an Urban Area of Southern Poland—Preliminary Research - Ewa Brągoszewska (Atmosphere, 2020)
The benefits of regular exercise include improved physical and mental health. The school gym is a particular micro-environment where students perform intensive physical training. The question is if there is an increased risk of microbiological contamination. This preliminary work studied the exposure of students to bacterial aerosol (BA) in a highschool gym located in an urban area of Southern Poland. A sampling of BA was undertaken with an Andersen six-stage impactor (ANDI). BA was identified using API (analytical profile index) tests. The BA concentrations were expressed as Colony Forming Units (CFU) per cubic metre of air. The results showed that before gym classes (BGC), the concentration of BA was 4.20 × 102 ± 49.19 CFU/m3, while during gym classes (DGC), the level of BA more than doubled (8.75 × 102 ± 121.39 CFU/m3). There was also an increase in the respirable fraction of BA (particles less than 3.3 µm). Before the start of the sports activities, respirable fraction accounted for 30% of the BA, while during physical education classes, this share increased to over 80%. Identification of BA species showed that the dominant group of bacteria in the indoor air of the gym BGC was Gram-positive rods (61%) and for DGC it was Gram-positive cocci (81%). We detected that one bacteria strain (Corynebacterium striatum) was classified into risk group 2 (RG2) according to Directive 2000/54/EC. Additionally, multi-antibiotic resistance (MAR) showed that among the isolated airborne bacteria, the highest antibiotic resistance was demonstrated by Staphylococcus epidermis (isolated DGC) and Pseudomonas sp. (isolated BGC). The quantitative and qualitative information on microbiological air quality (MIAQ) in the school gym indicates that the actions to improve indoor physical activity spaces are recommended.